Association between serum cytokine levels and the development of acute radiotoxicity in prostate cancer patients - Kopčalić, Katarina (Medicinski podmladak, 2024)
Radiotherapy plays a significant role in the multidisciplinary approach to treating prostate cancer patients. However, some of these patients may develop severe adverse effects after receiving radiotherapy that negatively affect their quality of life. Radiotoxicity may manifest in the lower gastrointestinal (GI) tract by damaging the rectum or bowel, or genitourinary (GU) tract, causing symptoms due to urethral, bladder or prostate damage. The probability of complications in normal tissue increases as the delivered radiation dose is increased. However, there are patients with satisfactory dosimetric parameters who develop radiation toxicity and vice versa. Prediction models that take into account additional parameters to identify patients most susceptible for developing toxicity may serve as essential factor toward a personalized RT. The main objectives are the morbidity reduction and life-quality improvement. Changes in the cytokines levels could also be connected with the occurrence of acute gastrointestinal and genitourinary toxicity. Literature data indicate the association of numerous cytokines with the appearing of GI and GU toxicity. There is proof that TGF- β1 stimulates fibroblasts to generate extracellular matrix. According to the literature, IL-6 is regarded as one of the most important immune markers for predicting the RT-induced toxicity of normal tissues. Increased IL-6 concentrations in the serum during radiotherapy are significantly linked to higher degree of acute genitourinary toxicity. It can be concluded that the radiation therapy, the development of an inflammatory process, and the occurrence of radiation toxicity are all related. However, further research with the aim of adequate stratification of patients for the development of an individualized approach to radiotherapy is required.